Affect Following First Exercise Session as a Predictor of Treatment Response in Depression - Suterwala, Anisha M. (J Clin Psychiatry, 2016)
OBJECTIVE: Remission rates are low with antidepressant treatments either as a first step or even with a second step. Furthermore, despite extensive investments from NIH and Industry, novel treatments are not yet available in clinical care for depression. Predictors of treatment response very early in the course of treatment can avoid unnecessarily lengthy trials with ineffective treatments and reduce the trial and error process. This paper examines the expression of positive affect immediately following an acute exercise session at the end of the first exercise session as a predictor of treatment response in the NIMH-funded TrEAD (Treatment with Exercise Augmentation for Depression) study, which was conducted from April 2003–August 2007. METHOD: 122 subjects with DSM-IV diagnosed Major Depressive Disorder were randomized to public health dose (16 kcal/kg/week or KKW) or low dose (4 KKW) of exercise for 12 weeks. Affect following the first exercise session was assessed using the Positive and Negative Affect Scale (PANAS) and depressive symptoms were assessed weekly using the Inventory for Depressive Symptoms – Clinician Rated (IDS-C). RESULTS: The PANAS Composite Affective (CA) score (positive - negative total) predicted change in IDS-C score (p < .05), as well as treatment response (p < .02) and remission (p < .03) for those in the high dose group but not in the low dose group. CONCLUSIONS: These findings suggest that the composite positive affect following the first exercise session has clinical utility to predict treatment response to exercise in depression and match the “right patient” with the “right” treatment. CLINICAL TRIALS REGISTRATION: Clinicaltrials.gov NCT00076258